SELECTIVITY OF RESIDUAL HERBICIDES USED IN SUGARCANE CROPS FOR CROTALARIA SPECIES - Souza, Renan Cantalice de; Santos, Hilda Rafaella da Silva; Farias, Ana Rosa de Oliveira; Santos, Leandro Lima Casado dos; Pereira, Mariângela Gomes; Silva Júnior , Antônio Barbosa da (Revista Científica da Faculdade de Educação e Meio Ambiente, 2023)
The use of herbicides for desiccation and with residual effect in sugarcane crops increases the spectrum of weed control, reducing the early interference of weeds in crops. Crotalaria species are commonly used for certain purposes, including weed suppression, but herbicides need to be applied to provide a better establishment ofthespecies. Given the above, the objective of this study was to determine the tolerance of Crotalaria species to pre-emergence herbicides used in sugarcane through dose-response curves, establishing the safest doses to be used. Greenhouse assays were conducted at the Campus of Engineering and Agricultural Sciences of the Federal Universityof Alagoas (CECA/UFAL), located in Rio Largo – AL. The experimental units consisted of recipients with a capacity of 500 ml filled with médium to heavy texture soil. Seeds of Crotalaria ochroleuca and Crotalaria spectabilis were sown directly in the recepients. Five herbicides were used in the experiment: flumioxazin (Flumyzin®), metsulfuron-methyl (Zartan®), clomazone (Reactor®), 2,4-D + picloram (Norton®) andisoxaflutole (Provence®). The experimental design was completely randomized in a 2 x 5 factorial arrangement, with four replications. The factors were two species of Crotalaria (C. ochroleuca and C. spectabilis) and five doses of herbicides (0; 50; 100; 200; and 400% of the dose recommended for sugarcane crops). One experimente was performed for each herbicide. A visual control evaluation was performed: 0% indicated the total absence of symptomsand 100% indicated the death of the plant. At the end of the experiment, the plants were collected for assessment of shoot and root dry mass. The experimental data weren submitted to analysis of variance using the SISVAR software and a non-linear regression model of the logistic type with 3 parameters was fit to the data. The results obtained showed that the herbicides clomazone and methsulfuron-methyl are safe for C. spectabilis, but C. ochroleuca tolerated doses below that recommended by the manufacturer. The species C. spectabilis and C. ochroleuca have moderate tolerance to the herbicide flumioxazin. The herbicide isoxaflutole is safe only for C. spectabilis and the herbicide 2,4-D + picloram is not recommended for any of the two species.